AMPA Receptor–mTOR Activation is Required for the Antidepressant-Like Effects of Sarcosine during the Forced Swim Test in Rats: Insertion of AMPA Receptor may Play a Role - Chen, Kuang-Ti; Tsai, Mang-Hung; Wu, Ching-Hsiang; Jou, Ming-Jia; Wei, I-Hua; Huang, Chih-Chia (Frontiers in Behavioral Neuroscience, 2015)
Sarcosine, an endogenous amino acid, is a competitive inhibitor of the type I glycine transporter and an N-methyl-D-aspartate receptor (NMDAR) coagonist. Recently, we found that sarcosine, an NMDAR enhancer, can improve depression-related behaviors in rodents and humans. This result differs from previous studies, which have reported antidepressant effects of NMDAR antagonists. The mechanisms underlying the therapeutic response of sarcosine remain unknown. This study examines the role of mammalian target of rapamycin (mTOR) signaling and α-amino-3-hydroxy-5-methylisoxazole-4-propionate receptor (AMPAR) activation, which are involved in the antidepressant-like effects of several glutamatergic system modulators. The effects of sarcosine in a forced swim test (FST) and the expression levels of phosphorylated mTOR signaling proteins were examined in the absence or presence of mTOR and AMPAR inhibitors. In addition, the influence of sarcosine on AMPAR trafficking was determined by analyzing the phosphorylation of AMPAR subunit GluR1 at the PKA site (often considered an indicator for GluR1 membrane insertion in neurons). A single injection of sarcosine exhibited antidepressant-like effects in rats in the FST and rapidly activated the mTOR signaling pathway, which were significantly blocked by mTOR inhibitor rapamycin or the AMPAR inhibitor 2,3-dihydroxy-6-nitro-7-sulfamoyl-benzo(f)quinoxaline (NBQX) pretreatment. Moreover, NBQX pretreatment eliminated the ability of sarcosine to stimulate the phosphorylated mTOR signaling proteins. Furthermore, GluR1 phosphorylation at its PKA site was significantly increased after an acute in vivo sarcosine treatment. The results demonstrated that sarcosine exerts antidepressant-like effects by enhancing AMPAR–mTOR signaling pathway activity and facilitating AMPAR membrane insertion. Highlights: - A single injection of sarcosine rapidly exerted antidepressant-like effects with a concomitant increase in the activation of the mTOR signaling